Optimizing Aesthetic Outcome of Anterior Implant with Provisional Restoration - Melisa; Adit Widaryono (TALENTA, 2025)
The replacement of missing teeth in the esthetic zone presents a significant challenge for dentists. Among the available treatment options such as fixed bridges and removable dentures implant-supported tooth replacement for a single edentulous site is often the preferred approach. To replicate the natural tooth contour in the cervical area, implant restoration requires a provisional restoration that serves as a tissue former, helping to mimic the shape of a natural tooth. Compared to stock healing abutments, this customized tissue former offers a distinct advantage in achieving optimal soft tissue contouring. In this case, a 40-year-old female patient complained about her right upper lateral incisor tooth (Tooth 12 is fractured). Anamnesis, along with extra- and intra-oral examinations, is conducted to assess the patient's condition. Additionally, 3D radiography is performed to evaluate the implant site and develop an appropriate treatment plan. To achieve a more ideal emergence profile and soft tissue contour, implant placement with a provisional resin restoration was chosen as the preferred approach. In conclusion, recognizing and managing peri-implant tissue is the key to long-term esthetic success. The use of provisional resin restoration is maintaining and preserving more bone and soft tissue in the implant area. The patient feels satisfied aesthetically and comfortable with the final restoration.